Statistical evaluation of very high cycle fatigue property of high carbon chromium bearing steel under axial loading. Issue 11 (23rd July 2016) - Li, W.; Sakai, T.; Deng, H.
Abstract : Axial loading test was performed to investigate the S–N characteristics and the failure mechanisms of a high carbon chromium bearing steel under very high cycle fatigue (VHCF). Compared with the experimental results under rotating bending, the bearing steel under axial loading also exhibited two failure modes including surface failure and interior inclusion-induced failure. In the life regime beyond about 10 6 cycles, the fine granular area can occur around the inclusion. But under the axial loading with the uniform stress distribution on the cross-section of specimen, the duplex S–N characteristics of bearing steel was not so distinct. In view of the limitation of common statistical method, a statistical method based on mixed Weibull distribution and parameter optimisation was proposed to evaluate the VHCF property of bearing steel corresponding to two failure modes. Based on the proposed statistical method, the P–S–N curves of bearing steel under axial loading can be better established. This paper is part of a Themed Issue on Recent developments in bearing steels.